Geomechanical model test for failure and stability analysis of high arch dam based on acoustic emission technique. (December 2018) - Wang, S.G.; Liu, Y.R.; Tao, Z.F.; Zhang, Y.; Zhong, D.N.; Wu, Z.S.; Lin, C.; Yang, Q.
Abstract: The internal damage of the model during the geomechanical model test is difficult to be detected. The failure and instability process of the arch dam are always accompanied by a large number of acoustic emission (AE) signals, which is related to the number of cracks in the model. AE technique was applied in the geomechanical model test of Mengdigou arch dam to analyze its failure process and overall stability. Noise filtering was conducted based on spectrum analysis of AE signal waveform. Parameter analysis was performed after noise filtering. The overall stability of the dam was evaluated by three characteristic overload safety factors: the crack initiation factor K 1, nonlinear deformation factor K 2 and ultimate load factor K 3, which were studied by AE parameter analysis. The failure process of Mengdigou arch dam was analyzed by the statistical analysis of AE hits and the wave velocity variation before and after test. AE analysis results were compared with the displacement and video monitoring results at the same time to verify the correctness of the evaluation method based on AE technique. The results showed that the failure process of the dam and foundation was well described by the AE technique, and the three safety factors of Mengdigou arch dam were defined more clearly. And as for Mengdigou arch dam, the fracture occurred at the dam heel area in the early stage of loading and the abutment of right bank was better than the left. The foundation damage was not serious after test and the overall instability was determined by instability of dam. Based on AE technique, the three overload safety factors was determined more clearly: K 1 = 1.5–2.0, K 2 = 4.5–5.0, and K 3 = 11–11.5, which provided an important reference for the Mengdigou arch dam construction.